A novel activity of microsomal epoxide hydrolase: metabolism of the endocannabinoid 2-arachidonoylglycerol - Nithipatikom, Kasem (The American Society for Biochemistry and Molecular Biology, 2014)
Microsomal epoxide hydrolase (EPHX1, EC 3.3.2.9) is a highly abundant α/β-hydrolase enzyme that is known for its catalytical epoxide hydrolase activity. A wide range of EPHX1 functions have been demonstrated including xenobiotic metabolism; however, characterization of its endogenous substrates is limited. In this study, we present evidence that EPHX1 metabolizes the abundant endocannabinoid 2-arachidonoylglycerol (2-AG) to free arachidonic acid (AA) and glycerol. The EPHX1 metabolism of 2-AG was demonstrated using commercially available EPHX1 microsomes as well as PC-3 cells overexpressing EPHX1. Conversely, EPHX1 siRNA markedly reduced the EPHX1 expression and 2-AG metabolism in HepG2 cells and LNCaP cells. A selective EPHX1 inhibitor, 10-hydroxystearamide, inhibited 2-AG metabolism and hydrolysis of a well-known EPHX1 substrate, cis-stilbene oxide. Among the inhibitors studied, a serine hydrolase inhibitor, methoxy-arachidonyl fluorophosphate, was the most potent inhibitor of 2-AG metabolism by EPHX1 microsomes. These results demonstrate that 2-AG is an endogenous substrate for EPHX1, a potential role of EPHX1 in the endocannabinoid signaling and a new AA biosynthetic pathway.